1991
DOI: 10.1093/geronj/46.1.p31
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Influence of Intelligence and Age on Everyday Memory

Abstract: A short memory test that provides analogs of everyday activities was used to investigate the relationship between everyday memory, cognitive abilities, participation in social, domestic, and leisure pursuits, and health status among 94 community-dwelling people aged between 70 and 93 years. Multiple regression analysis revealed that while fluid intelligence was a significant predictor of performance on most of the memory items, age was also a significant predictor of performance on prospective and verbal memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
64
1
6

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 0 publications
7
64
1
6
Order By: Relevance
“…The value used in our models was the number of correctly noted patterns. Previous research has demonstrated that fluid abilities, such as inductive reasoning, are significantly related to memory performance (Cockburn & Smith, 1991).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value used in our models was the number of correctly noted patterns. Previous research has demonstrated that fluid abilities, such as inductive reasoning, are significantly related to memory performance (Cockburn & Smith, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…The value used in our models was the number of correctly noted patterns. Previous research has demonstrated that fluid abilities, such as inductive reasoning, are significantly related to memory performance (Cockburn & Smith, 1991).Verbal Knowledge-The measure of crystallized verbal knowledge included in the ACTIVE battery was a multiple choice vocabulary test from the Kit of Factor-Referenced Cognitive Tests (Ekstrom, French, Harman, & Derman, 1976). Participants were presented with a stimulus word, and asked to select a synonym from among five choices.…”
mentioning
confidence: 99%
“…Others have focused on the specific characteristics of prospective memory, such as strategy use (Harris, 1980), the role of event-cues in prospective remembering (Ellis, Kvavilashvili, & Milne, 1999), Personality and prospective memory 4 developmental aspects of prospective memory (Beal, 1988), as a framework for everyday forgetting (Cavanaugh, Grady, & Perlmutter, 1983;Lovelace & Twohig, 1990;Marsh, Hicks, & Landau, 1998), and age-related changes in prospective remembering (Einstein, McDaniel, Richardson, Guynn & Cunfer, 1995;Mantyla, 1994;Maylor, 1990;. For example, there is good evidence of age-related prospective memory decline when laboratory or computer generated tasks are used (Cockburn and Smith, 1991;Craik, 1992;Uttl and Graf, 2000), with older adults showing more prospective memory errors than younger adults. However, a different pattern emerges when questionnaires or everyday measures are used to assess prospective memory, with older adults performing as well as younger adults, but this may be due to the fact that the older adults use more strategies to aid remembering in a real-world context (see Baddeley, 1997).…”
Section: Dimension On Prospective Memorymentioning
confidence: 99%
“…been observed that are, at least in some respects, more striking than age deficits in RM performance (e.g., Cockburn & Smith, 1991;Mäntylä & Nilsson, 1997;Maylor, 1993aMaylor, , 1996a. However, in other cases, equivalentPM performance in young and older adults has been found in the context of age-related decline in RM performance (e.g., Einstein & McDaniel, 1990;Maylor, 1990).…”
mentioning
confidence: 99%